OC-080 Ibd-Sshamp (Supported, Self help and Management Programme); UK'S first Internet based Remote Management System for Managing Stable IBD. (4th June 2013) - Johnson, M W; Lithgo, K; Price, T
Abstract : Introduction: In February 2012 the Luton & Dunstable University Hospital in Hertfordshire, became the first hospital in UK to commence a remote management programme for stable inflammatory bowel disease (IBD) patients. The project, entitle IBD-SSHAMP (Supported, Self Help And Management Programme), was funded by an Innovation Award presented by the East of England Primary Care Trust (PCT) Innovation Team. The aim was to discharge patients from routine clinic visits, whilst maintaining an efficient remote monitoring system that could be co-ordinated through our specialist nurses. Methods: The first stage was to ensure we had a complete and up-to-date database containing all of our IBD patients. After a retrospective 10 year review we identified a total of 2790 IBD patients, from 19 different ethnic backgrounds. Of these, 26 patients lacked mental capacity with learning disability or dementia and 117 did not have internet access. 370 of our original cohort had died by the time of commencing the project. Using Patient Knows Best we developed individualise websites to offer a communication portal between patients and specialist care, through which we could monitor their symptoms and offer management advice through a traffic light system. An alert is sent out to the IBD nurses and clinician involved if any patients symptom indices deteriorate markedly. Periodic faecal calprotectin and inflammatory markers will also be used to support the monitoring process. Virtual clinics will be held for these patients twice a year. If necessary patients can be seen in hospital clinics usually within 24–48 hrs. Results: Of the available 2, 277 IBD patients, we have successfully discharged 400 onto the first wave of IBD-SSHAMP, with a further 300 due to follow shortly in the second wave. With confidence in the system building amongst the relevant clinicians the second wave will primarily contain patients stable on immunosuppressants eg. azathioprine. With most patients being seen at 6 monthly intervals, and follow up clinic appointments costing our PCT £85, this project could potentially save them £119, 000 per year, whilst still providing a patient friendly and efficient management system. Conclusion: IBD-SSHAMP is the UK's first internet based remote management system for managing stable IBD patients. It aims to reduce cost and free up NHS outpatient time, whilst providing an efficient monitoring and management programme. This is a proof of concept project, from which further data outcomes will be presented. Disclosure of Interest: None Declared